2021
DOI: 10.1038/s41598-021-87746-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial static magnetic stimulation over the primary motor cortex on local and network spontaneous electroencephalogram oscillations

Abstract: Transcranial static magnetic stimulation (tSMS) is a novel non-invasive brain stimulation technique that reduces cortical excitability at the stimulation site. We investigated the effects of tSMS over the left primary motor cortex (M1) for 20 min on the local electroencephalogram (EEG) power spectrum and interregional EEG coupling. Twelve right-handed healthy subjects participated in this crossover, double-blind, sham-controlled study. Resting-state EEG data were recorded for 3 min before the intervention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…tSMS is based on the transcranial application of a static magnetic field (120-200 mT at 2-3 cm from the magnet surface) (Rivadulla et al, 2014) over the skull. Recently, a number of studies applying tSMS over different cortical areas (e.g., visual, motor, supplementary motor and somatosensory cortices) have demonstrated neurophysiological and/or behavioral effects in healthy subjects and patients (Arias et al, 2017;Carrasco-López et al, 2017;Dileone et al, 2018;Gonzalez-Rosa et al, 2015;Kirimoto et al, 2020Kirimoto et al, , 2018Kirimoto et al, , 2014Lacroix et al, 2019;Lozano-Soto et al, 2018;Nakagawa et al, 2019;Nakagawa and Nakazawa, 2018;Nojima et al, 2019Nojima et al, , 2016Oliviero et al, 2011;Sheffield et al, 2019;Shibata et al, 2021;Silbert et al, 2013;Soto-León et al, 2022). These studies support the main idea that tSMS has general inhibitory effects by a reduction in the neuronal excitability, and one of the proposed mechanisms for this to happen is a mechanical mechanism (Hernando et al, 2020).…”
Section: Introductionmentioning
confidence: 59%
“…tSMS is based on the transcranial application of a static magnetic field (120-200 mT at 2-3 cm from the magnet surface) (Rivadulla et al, 2014) over the skull. Recently, a number of studies applying tSMS over different cortical areas (e.g., visual, motor, supplementary motor and somatosensory cortices) have demonstrated neurophysiological and/or behavioral effects in healthy subjects and patients (Arias et al, 2017;Carrasco-López et al, 2017;Dileone et al, 2018;Gonzalez-Rosa et al, 2015;Kirimoto et al, 2020Kirimoto et al, , 2018Kirimoto et al, , 2014Lacroix et al, 2019;Lozano-Soto et al, 2018;Nakagawa et al, 2019;Nakagawa and Nakazawa, 2018;Nojima et al, 2019Nojima et al, , 2016Oliviero et al, 2011;Sheffield et al, 2019;Shibata et al, 2021;Silbert et al, 2013;Soto-León et al, 2022). These studies support the main idea that tSMS has general inhibitory effects by a reduction in the neuronal excitability, and one of the proposed mechanisms for this to happen is a mechanical mechanism (Hernando et al, 2020).…”
Section: Introductionmentioning
confidence: 59%
“…The fourth limitation is the need for more clarity regarding the remote brain effect. The researcher reported that tSMS can not only suppress brain function directly under the magnet but also induce various remote effects through brain networks ( Shibata et al, 2021 ; Takamatsu et al, 2021 ). However, this study only measured the rPFA cortex, and the impact of tSMS on this area that extends to other brain regions warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Theta band has been previously associated with tactile function, namely in roughness discrimination (Genna et al, 2017(Genna et al, , 2018. Alternatively, such theta modulation could also reflect some form of interaction between the somatosensory and the motor cortex (Shibata et al, 2021) as expected from the change occurring between the tactile discrimination period and the response period (more associated "Task description" the electrodes presenting modulations between the discrimination and response periods are presented. "Tactile discrimination" the networks of electrodes that are correlated with performance "between-subjects" and "within-subjects" are presented.…”
Section: Discussionmentioning
confidence: 99%